Associations between patterns of physical activity, pain intensity, and interference among older adults with chronic pain: a secondary analysis of two randomized controlled trials - Fanning, Jason; Brooks, Amber K.; Robison, Justin T.; Irby, Megan B.; Ford, Sherri; N’Dah, Kindia; Rejeski, W. Jack (Frontiers in Aging, 2023)
Background: Clinical management of chronic pain often includes recommendations to engage in physical activity (PA), though there are little data on the interplay between pain symptoms and key aspects of PA participation (e.g., intensity and bout duration) among older adults. Herein we investigate the longitudinal relationships between changes in PA behavior and changes in pain intensity and interference among low-active older adults with obesity and chronic pain. Methods: Participants (N=41) were enrolled in two randomized pilot trials wherein they were assigned to an intervention focused on participation in frequent PA across the day, or to a low-contact control. Participants completed the 3-item PROMIS pain intensity scale and 8-item PROMIS pain interference scale before and after the interventions. Participants also wore an ActivPAL accelerometer for 7 days before and during the final week of the interventions. Results: A series of linear regression analyses demonstrated that increased time spent stepping at a high-light intensity in very short bouts was associated with increased pain intensity scores. By contrast, increased time spent stepping at a high-light intensity in bouts of 5-20 minutes was associated with reductions in pain intensity and interference scores. Increased time spent stepping at a moderate intensity overall was associated with reduced pain intensity scores, and time spent stepping at a moderate intensity for 10-20 minutes associated with reduced pain interference. Conclusions: These findings suggest older adults with chronic pain may benefit by moving at high-light or moderate intensities in brief bouts of at least 5 minutes in duration.